Implementasi Method of Successive Interval untuk Strategi Pengelolaan Sampah yang Berkelanjutan - Herdianzah, Yan; Riana, Riska Iva; Immawan, Taufiq; Wahyuni P, A Dwi; Ahistasari, Asih (Universitas Muhammadiyah Sorong, 2024)
The solid waste section of Manggala District, Makassar City, currently still finds many risks that commonly occur in the waste management supply chain from the waste source to the Temporary Disposal Site (TPS) then to the Final Disposal Site (TPA). This causes the volume of waste to increase every day due to the lack of waste sorting from the waste source so that the waste in the TPS is scattered due to the waste bins no longer being able to accommodate it and ultimately the TPA experiences over capacity without any effective handling to reduce the volume of waste. Therefore, it is necessary to deal with the risks that occur. This research aims to provide suggestions for sustainable mitigation strategies to reduce the impact of risks on waste management using the Delphi method to identify potential risks. Using the House of Risk (HOR) at the risk analysis and evaluation stage to determine mitigation strategies and measuring the sustainability index using the Successive Interval (MSI) Method to determine the sustainability status of the proposed mitigation strategy. Based on the research results, it is known that there are 18 risk events and 65 risk agents identified. Next, a mitigation strategy was carried out on the risk agent using 16 preventive actions, which then measured the level of sustainability of each strategy. The results of these measurements found 3 strategies whose status was very sustainable, 10 strategies whose status was quite sustainable and 3 strategies whose status was less sustainable.